Gross total resection and adjuvant radiotherapy most significant predictors of improved survival in patients with atypical meningioma. Issue 4 (13th November 2017) - Rydzewski, Nicholas R.; Lesniak, Maciej S.; Chandler, James P.; Kalapurakal, John A.; Pollom, Erqi; Tate, Matthew C.; Bloch, Orin; Kruser, Timothy; Dalal, Prarthana; Sachdev, Sean
Abstract : BACKGROUND: Atypical and malignant meningiomas are far less common than benign meningiomas. As aggressive lesions, they are prone to local recurrence and may lead to decreased survival. Although malignant meningiomas typically are treated with maximal surgical resection and adjuvant radiotherapy (RT), to the authors' knowledge the optimal treatment for atypical lesions remains to be defined. There are limited prospective data in this setting. METHODS: The National Cancer Data Base was queried to investigate cases of histologically confirmed meningiomas diagnosed from 2004 to 2014. This included 7811 patients with atypical meningiomas (World Health Organization grade 2) and 1936 patients with malignant meningiomas (World Health Organization grade 3); during the same period, a total of 60, 345 patients were diagnosed with benign meningiomas (World Health Organization grade 1). Data collected included patient and tumor characteristics, extent of surgical resection, and use of RT. Survival analysis was performed using Kaplan‐Meier estimates with the log‐rank test of significance and Cox univariate and multivariate regression. Logistic regression was used to determine factors associated with use of RT. RESULTS: The 5‐year overall survival rate was 85.5% in patients with benign meningiomas, 75.9% in patients with atypical meningiomas, and 55.4% in patients with malignant meningiomas ( P <.0001). In patients with atypical meningiomas, gross (macroscopic) total resection (GTR) and adjuvant RT were found to be associated with significantly improved survival, independently and especially in unison (GTR plus RT: hazard ratio, 0.47; P = .002). On multivariate analysis, the combination of GTR plus RT was found to be the most important factor for improved survival. However, GTR was associated with significantly lower rates of RT use. CONCLUSIONS: GTR and adjuvant RT appear to be highly associated with improved survival, independent of other factors, in patients with atypical meningiomas. Cancer 2018;124:734‐42. © 2017 American Cancer Society . Abstract : Atypical meningiomas are rare and aggressive lesions that are prone to local disease recurrence and worse survival compared with benign meningiomas, and to the authors' knowledge their optimal management is not defined. Gross total resection and adjuvant radiotherapy appear to be highly associated with improved survival, independent of other factors.